Exact Solutions to the Symmetric and Asymmetric Vehicle Routing Problem with Simultaneous Delivery and Pick-Up - Julia Rieck; Jürgen Zimmermann (BuR - Business Research, 2013)
In reverse logistics networks, products (e.g., bottles or containers) have to be transported from a depot to customer locations and, after use, from customer locations back to the depot. In order to operate economically beneficial, companies prefer a simultaneous delivery and pick-up service. The resulting Vehicle Routing Problem with Simultaneous Delivery and Pick-up (VRPSDP) is an operational problem, which has to be solved daily by many companies. We present two mixed-integer linear model formulations for the VRPSDP, namely a vehicle-flow and a commodity-flow model. In order to strengthen the models, domain-reducing preprocessing techniques, and effective cutting planes are outlined. Symmetric benchmark instances known from the literature as well as new asymmetric instances derived from real-world problems are solved to optimality using CPLEX 12.1.
urn:nbn:de:0009-20-36470
Keywords: 650; mixed-integer linear programming; reverse logistics; simultaneous delivery and pick-up; vehicle routing; Tourenplanung; Betriebliche Kreislaufwirtschaft; Lieferkette; Transportlogistik; Mathematische Optimierung